2013
DOI: 10.1007/s00405-013-2448-6
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of cone beam computed tomography in scalar localization of the electrode array: a radio histological study

Abstract: Postoperative imaging plays a growing role in clinical studies concerning prognostic factors in cochlear implantation. Indeed, intracochlear position of the cochlear implant has recently been identified as a contributor in functional outcomes and radiological tools must be accurate enough to determine the final placement of the electrode array. The aim of our study was to validate cone beam computed tomography as a reliable technique for scalar localization of the electrode array. We performed therefore a temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…Theoretical positions of scala tympani and scala vestibuli were determined based on previous studies [Lecerf et al, 2011;Marx et al, 2014]. On midmodiolar reconstructions, scala tympani was localized in the inferior part of a half-turn section of the cochlea and scala vestibuli in the superior part.…”
Section: Imaging Studymentioning
confidence: 99%
“…Theoretical positions of scala tympani and scala vestibuli were determined based on previous studies [Lecerf et al, 2011;Marx et al, 2014]. On midmodiolar reconstructions, scala tympani was localized in the inferior part of a half-turn section of the cochlea and scala vestibuli in the superior part.…”
Section: Imaging Studymentioning
confidence: 99%
“…Besides high-resolution computed tomography (3,12), cone beam computed tomography (CBCT) (13) has gained increasing support as it is a quick procedure and the radiation dose seems to be lower than with high-resolution computed tomography (14). Furthermore, previous reports have shown high reliability for correctly detecting scalar position of the electrode array within the basal turn of the cochlea (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…According to the histologic study of Marx et al, 11 the electrode position within the cochlea can be reliably identified. When one knows that in multiplanar reconstructions, the tympanic scala is basal and the vestibular scala is apical, the liquid-filled space is seen above the electrode array when the electrode is located correctly in the scala tympani.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high resolution and low influence of metal artifacts, CBCT has emerged as a reliable technique in scalar localization of the electrode array, showing a sensitivity of 100% and specificity of 90%. 11 According to Aschendorff et al, 1 the intracochlear localization of the electrode has a significant impact on speech recognition. Insertion of the electrode array in the scala tympani is associated with a better outcome than insertion in the scala vestibuli.…”
mentioning
confidence: 99%